Therapeutic Value of CD73 as a Biomarker in Human Cancer - Zandieh, Kimia; Millani, Saeideh; Mohammadi, Javad; Hashemi, Mehrdad (Archives of Advances in Biosciences, 2019)
Context: Over the past several years, biomarkers have emerged as a diagnostic and therapeutic tool for cancer therapy. CD73 (ecto-5'-nucleotidase) which is a cell surface ectonucleotidase, mediates the conversion of extracellular Adenosine monophosphate (AMP) into adenosine through the purinergic signaling pathway. In this study the role of CD73 in different human cancers was investigated. Evidence Acquisition: The present study reviewed the articles related to the importance of CD73 as a therapeutic tool in human cancers which were published from 1990 to 2019. The publications were found by searching the valid databases for instance PubMed, Google Scholar, ProQuest, Scopus and Science Direct using keywords CD73, ectonucleotidase, therapy, cancer, etc. During the review process 90 articles were selected. Results: Different studies about the effect of CD73 on human malignancies show that CD73 is overexpressed in various types of cancer. Recent findings demonstrate that the extracellular adenosine can promote tumor growth and invasion. The significant regulatory role of CD73 has made it a suitable biomarker for cancer treatment. Conclusion: This study outlines the impact of CD73 on tumor growth, metastasis and angiogenesis. The findings are promising and can highlight the efficacy of this protein as a therapeutic tool in the context of anti-CD73 cancer therapy.